Petrologia e geoquímica do Batólito Shoshonítico Serra do Brejo no domínio Poço Redondo, Faixa Sergipana (sul da Província Borborema) - Gentil, Talita Fernanda Carvalho (2013)
The area of this study is located in the Northern sector of the Sergipana Belt. The Serra do Brejo batholith (BSB) is associated to the Serra Catu magmatism, which is assigned by the regional literature as a post-tectonic plutonism, aged ~ 617 Ma. The BSB is an E-W elongated body, ~ 111 km2, that truncates the NW-SE regional structures. The aim of this work is to provide geological, petrographic and geochemical data for the BSB in order to identify its features and better understand the significance of this magmatism in the context of the Sergipana Belt. Field work, sample collection, petrographic description of the main rock types, and geochemical studies were performed. Three lithologic facies have been identified: (i) Granitic, (ii) Syenitic/mafic Syenitic and (iii) Enclaves. At the microscope the most prominent feature is the significant phaneritic texture, sometimes exhibiting magmatic foliation, and subhedral crystals of alkali feldspar (orthoclase and microcline) albite or oligoclase. Mafic mineralogy includes diopside, hornblende and biotite, besides the presence of titanite, apatite and, in some samples, zircon. The Enclave Facies was interpreted as an autholit phase, by presenting the same mineralogy as the host rocks. The geochemical data shows that these rocks compositions are comprised between 60-70% SiO2, except for the Enclave Facies that ranges hom 43-45% SiO2 (corresponding to gabbro peridotite) to 52-55% of SiO2 (corresponding to gabbro and diorite). In classification diagrams, these samples show alkaline and sub-alkaline signatures, typical of shoshonitic associations. They have metaluminous and peraluminous character and, in Pearce diagrams (Rb vs. Nb +Y), the samples are positioned predominantly in the field of granites that originate in volcanic arc environments, been concentrated in the field of post tectonic granites. It is concluded that the magmas forming the rocks studied (trachytic and basaltic) has signed orogenic, and yet puts up after the peak of the orogeny that affected the Sergipana Belt.